Different effects of local and landscape factors on the population density of two fruit fly species in Indonesian apple orchards - SHERLITA OCTAVINA RACHMA PUTRI; AKHMAD RIZALI; SILVI IKAWATI (Society for Indonesian Biodiversity, 2025)
Abstract. Putri SOR, Rizali A, Ikawati S. 2025. Different effects of local and landscape factors on the population density of two fruit fly species in Indonesian apple orchards. Biodiversitas 26: 2079-2087. Apple production in Indonesia faces significant challenges due to pests, particularly fruit flies (Diptera: Tephritidae). Recently, management strategies for controlling fruit flies in apple orchards have often overlooked the influence of local and landscape-level factors. The objective of this study is to investigate how these factors affect fruit fly population densities in apple orchard. Research was conducted in nine apple orchards in East Java, Indonesia. For each orchard, the landscape was characterized by manual digitization the area within a 500 m radius from the center of the plot. To sample fruit flies, attractant traps were used along with rearing symptomatic fruits. Three species of fruit flies were identified in the apple orchards, with Bactrocera carambolae and B. dorsalis being the most abundant. In contrast, B. umbrosa was found only in one research site. Using Generalized Linear Model (GLM) analysis, it was determined that local factors, such as the frequency of pesticide application and canopy cover), as well as landscape factors, including class area and the number of patches of semi-natural habitats and apple orchards, influenced the population density of B. carambolae. On the other hand, B. dorsalis was only affected by a landscape factor, specifically class area of semi-natural habitats. Spatial variation of B. carambolae within the apple orchards was also influenced by a local factor (canopy cover) and a landscape factor (class area of semi-natural habitats). However, B. dorsalis was not affected by either type of factor. These findings emphasize the importance of understanding local and landscape factors to develop effective management strategies for different species of fruit flies in apple orchards.